HEALTH FINANCING LAW AND DIGITALIZATION OF HEALTH SERVICES - Toga Adi Putra Sinaga; Rahmayanti (Journal of International Islamic Law, Human Right and Public Policy, 2024)
financing and the provision of health services. This journal explores the interaction between health financing legal regulations and the digitalization of online health services in Indonesia. The study aims to analyze how current regulations govern these two aspects and identify the challenges and solutions needed. Digitalization of health services, including the use of information technology such as electronic medical records (EMRs), telemedicine, and health applications, has significantly altered the healthcare landscape. This transformation presents new legal challenges, especially concerning health financing and personal data protection. This article discusses the interaction between digitalization and health financing regulations in Indonesia, focusing on how health laws and related policies address both aspects. It also explores the impact of digitalization on the management of health financing, patient rights, and provider responsibilities. Referring to Law No. 36 of 2009 on Health, Law No. 27 of 2022 on Personal Data Protection, and other regulations, this article provides an in-depth analysis of the need for regulatory adjustments to ensure effective integration of technology into the health system while maintaining the sustainability of financing and protecting patient rights. The methodology includes literature review, regulatory analysis, and case studies. Findings indicate that while digitalization offers improved efficiency and accessibility, there are regulatory challenges that need to be addressed to ensure effective integration between health financing systems and digital technology. Recommendations suggest updating regulations to create a more inclusive and secure system.